GOOGLE MAPS AND MOBILE DEVICES: CAN JUST ONE GENERIC DESIGN WORK? - Cartwright, William (Revista Brasileira de Cartografia, 2009)
The phenomena that is Google Map® has both made mapping more visible and made access to base maps more immediate. The proliferation of mash-ups and other Web-delivered map products that are based on Google maps illustrates this 'use-it-for-everything mapping phenomena. But, can Google's maps be used for everything, including mobile and small-format map delivery platforms? Can we just 'Google it?This paper discusses how user/producers have exploited the availability and accessibility of base maps from Google. It explores the numerous small format / mobile applications that have been developed and the content that they deliver. Then it considers whether it is appropriate and 'good' design practice to accept Google maps as an 'underlay' for developing this genre of map products.